Evaluating the impact of official development assistance on ecological environments in agricultural and renewable energy sectors - Rongrong Li; Jiaqi Guo; Qiang Wang (Humanities & Social Sciences Communications)
Abstract This study examines the complex interactions between official development assistance (ODA) and the ecological environment of recipient countries, mainly focusing on agricultural economic development and renewable energy. Using dynamic threshold models and robust statistical methods, the analysis uncovers the nuanced effects of ODA across various dimensions. Findings suggest that ODA has different impacts on the ecology of African countries depending on their agricultural dependence and renewable energy development levels. The study highlights the importance of targeted aid and advocates for the integration of ODA with environmentally sustainable development goals. Furthermore, the research underscores the potential for environmental improvement in countries with significant agricultural reliance. It emphasizes the critical role of renewable energy in mitigating ecological pressures and adapting to climate change. This study contributes to the assessment of sustainable development performance after the expiration of the United Nations Sustainable Development Goals in 2030.